‘If they are as thirsty as all that, let them come down to the pool’: unearthing ‘Wildlife’ history and reconstructing ‘Heritage’ in Gonarezhou National Park, from the late nineteenth century to the 1930s (Historia, 2021)
Since the Gonarezhou National Park was formed in 1975, the ‘natural’ environment image of wild animals, plants and geophysical features has dominated the way it is perceived as a tourist resort and as a national heritage ‘site’. However this ‘national park’ isonly a phase of the area’s history, and represents one dimension of a complex and changing perception of nature by man. In this paper I consider Gonarezhou not so much as natural space but as human-animal space in which the dominance of mankind over the last two or so centuries has imposed varying paradigms of heritage. Wildlife is a central part of these constructs, in whichhumankind “adapted and altered”1the environment around him/her and made it an ‘owned and controlled’ domain with or without the consent of other non-human living species. This sense of ownership, very often passed on to ‘future generations’, is what I define as heritage. It is the manner in which such ‘ownership and control’ of the wildlife environment was perceived and exercised in the pre-colonial and colonial periods that forms the crux of this paper. I argue that whereas pre-colonial space was not demarcated into separate human and game space, the first thirty years or so of colonial rule in Zimbabwe were characterized by evolving separate human-wildlife spheres that, in many ways, were influenced by contemporary wildlife policy and heritage. I view wildlife heritage not as a colonial creation but as emerging in the pre-colonial period and continuing in the colonial and post-colonial periods in a different cross-cultural and multi-racial environment.
Keywords: Natural park; National park; Gonarezhou; Heritage; Pre-colonial; Colonial; Natural resources; African culture; Elephant; Wildlife; Limpopo; transfrontier; tourism; conservation; Hunters